PENGEMBANGAN SISTEM INFORMASI SELEKSI BEASISWA UNGGULAN P3SWOT KEMDIKNAS ONLINE MENGGUNAKAN UNIFIED PROCESS - Khadijah Khadijah; Priyo Sidik Sasongko; Edy Suharto; A.B. Susanto (Department of Informatics, Universitas Diponegoro, 2011)
The Ministry of National Education has declared excellence scholarship program, one kind of these excellence scholarships is P3SWOT. P3SWOT is an excellence scholarship given to researcher, writer, creator, artist, journalist, athlete, and figure. As a holder of P3SWOT excellence scholarship, the Secretary of Excellence Scholarship, Bureau Planning and International Cooperation, the Ministry of National Education has been taking the advantage of the information technology by building a website that provides registration information, a registration form that can be downloaded by registrant, and the announcement of the scholarship winners. However, the website is not optimal because it is static. The selection mechanism of P3SWOT excellence scholarship still has some problems. Recently there are ineffective registration and unintegrated scholarship registration data. The online selection of P3SWOT excellence scholarship information system was developed to solve those problems. This information system was developed using Unified Process. Unified Process is an object oriented software development process that consists of five workflows. They are requirement, analysis, design, implementation, and test. This information system was built using PHP 5 programming language and MySQL 5 database management system. This information system can be used to handle the selection of P3SWOT excellence scholarship including registration, registration verification and scoring, deciding the winners, and reporting.